Migraine without Aura Correlation with Anxiety Level and Socio- Demographic Characteristics - Khalid Al-Quliti (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Different types of migraine may be studied separately to understand their epidemiology and pathophysiology better. No studies have investigated patients with associated factors of anxiety severity in migraine without auras. Therefore, in this study, anxiety and its associated factors were investigated in a sample of Saudi Arabian patients with migraine without aura. Methods: A cross-sectional study of 122 conveniently sampled migraine patients at Madinah hospitals, Saudi Arabia, completed the Generalized anxiety disorder-7 scale (GAD-7), and a tool for social, demographics, and clinical information. Results: The majority of patients who did not have an aura with their migraine were female (67.2%); many did not report participating in sports activities (58.2%), or have a family history of migraine-headaches (74.6%). Anxiety severity was higher in migraine-without-aura patients, and those undergoing treatment for co-morbid conditions (β = .547, p = .042), those without family history of migraine/chronic headache (β = .016, p = .016), and patients with high frequency of migraine medication use (β = .009, p = .009). Discussion: The correlation of the anxiety severity level in patients who have migraines without aura may have important clinical, and epidemiological implications. females with their change in hormonal stat have a higher prevalence of migraine without aura, those with no habitual sport activity, and family history of migraine may indicate the need for targeted screening for migraine in these groups.